Teknologi Mesin Pencacah Pakan Ternak Bergerak Terpadu di Pesantren Aufia Gibs Desa Minas Jaya, Minas, Siak - Yusnita Rahayu; Firdaus Firdaus; Rahmat Rizal Andhi; Ibrahim As; Fajrinnida Desfitri; Anjli Wulandari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The farm sector is the sector that has the most potential in the progress of the Aufia pesantren. So far, farms in the Aufia Islamic boarding school are only given whole animal feed from the weeds found in the pesantren. This is certainly not effective because as time goes on and when the farm is growing, it will be difficult to get maximum animal feed. So we need a chopper technology to destroy food waste and agricultural products that have not been utilized which can then be consumed by the animals. The purpose of this activity is to optimize the potential of pesantren by processing an integrated mobile feed system to meet the nutrition and quantity of growth and development of sheep. This chopper machine can chop animal feed ingredients in the form of leaves and weeds in the pesantren environment more optimally. The research method used is the socialization of the chopping machine and continued with demonstrations on the use of the chopper and the fermentation process. The result of this activity is that the chopper machine functions well and can chop animal feed raw materials in the form of weeds, palm leaves and other plants perfectly, easy to operate and move by the students at the pesantren which will then be fermented for long-term storage.